On the Relative Completeness of Bytecode Analysis versus Source Code Analysis - Logozzo, Francesco; Fahndrich, Manuel (Proceedings of the International Conference on Compiler Construction, 2008)
We discuss the challenges faced by bytecode analyzers designed for code verification compared to similar analyzers for source code. While a bytecode-level analysis brings many simplifications, eg, fewer cases, independence from source syntax, name resolution, etc., it also introduces precision loss that must be recovered either via preprocessing, more precise abstract domains, more precise transfer functions, or a combination thereof. The paper studies the relative completeness of a static analysis for bytecode compared to the analysis of the program source. We illustrate it through examples originating from the design and the implementation of Clousot, a generic static analyzer based on Abstract Interpretation for the analysis of MSIL.